SYSTEMATIC LITERATURE REVIEW INNOVATION MODEL AS A MEDIATING AND MODERATING VARIABLE IN MSMEs PERFORMANCE - I Wayan Sukania; Agustinus Purna Irawan; Fransisca Iriani Roesmala Dewi (Graduate Program of Universitas Tarumanagara, 2024)
Systematic literature reviews that focus on research on innovation variables as moderating and mediating exogenous variables on the performance of Micro, Small and Medium Enterprises (MSMEs) are still relatively rare. Therefore, the aim of this research is to determine the factors that influence MSME performance which are mediated or moderated by innovation variables. This type of qualitative research uses the Systematic Literature Review method. Article data collection comes from the Google Scholar database. Based on the search results, 180 articles were obtained from 2015 to 2024. After selecting and adjusting them to the research objectives, 30 articles were obtained. The results of this research show that factors influencing MSME performance are mediated by innovation variables including business networks, competitor orientation, market orientation, learning orientation, marketing strategies, entrepreneurial characteristics, business capital, entrepreneurial orientation, entrepreneurial competencies, learning capital, learning capability, technology orientation , technological capability, transactional capability, innovation-oriented technology assimilation strategy, human resource information system, leadership, relational capability, knowledge management, relational capability, market orientation, administrative innovation strategy, customer orientation, market orientation, and HRM. Other findings also found that factors influencing MSME performance were moderated by innovation variables, including supply chain management practices, learning orientation, market orientation, total quality management, and social media adoption. Factors influencing innovation performance which are moderated by innovation variables include open innovation, social media strategic capability, and innovation culture. This research provides recommendations for MSME players to be able to utilize various innovation models or variables to further develop and have competitiveness. This research provides suggestions for future researchers in conducting SLR regarding MSME Innovation and Competitive Advantage by focusing on the Moderation model.